Sedimentary environmental evolution in the western bohai sea since the middle pleistocene: integrating geochemical and paleontological records - Wu, Shuyu; Chu, Hongxian; An, Maoguo; Feng, Yongcai; Liu, Jun (Frontiers in Earth Science, 2025)
Aiming to address under-utilized geochemical proxies in the Bohai Sea (BS) due to analytical complexity and diagenetic uncertainty, this study present a 300-kyr high-resolution geochemical and microfossils records from core DZQ01, and identified elemental proxies such as Rb/Sr, Mg/Ca, and Ni/Co ratios to quantify paleoclimate, paleosalinity, and paleoredox variabilty. Six depositional units (DU6–DU1) are identified: DU6 (300–272 cal. ka B.P.) record cold-arid fluvial deposition, and persistent suboxic conditions; DU5 (272–205 cal. ka B.P.) captures an initial shift toward warmer, more humid conditions followed by renewed cooling and arid conditions, recorded in tidal-flat to shallow-marine facies; DU4 (205–90 cal. ka B.P.): is dominated by cold and arid conditions punctuated by a short-lived warming event; DU3 (90–57 cal. ka B.P.) exhibits elevated temperatures and sea levels, fully marine conditions marked by abundant benthic foraminifera and ostracods; DU2 (57–14 cal. ka B.P.) documents cold-arid conditions, incised-valley fills, and diminished biogenic activity; and DU1 (14 cal. ka B.P. to present) reflects warm-humid climate, widespread euryhaline assemblages, and high biological productivity in intertidal to shallow-marine setting. Glacial-interglacial cycles in BS are driven by orbital forcing, greenhouse gases, and ocean-atmosphere feedbacks, with glacials cooling/expanded ice sheets and interglacials warming/reconfigured circulation.